2010
DOI: 10.1080/17470210903134351
|View full text |Cite
|
Sign up to set email alerts
|

Similarity is closeness: Metaphorical mapping in a conceptual task

Abstract: The conceptual metaphor theory states that abstract concepts are represented by image schemas from concrete domains. In the present study we investigated the mapping for SIMILARITY IS CLOSENESS using tasks with nonlinguistic materials. In Experiments 1 and 2 participants decided whether two squares were similar or dissimilar in colour. The spatial distance between the squares was varied. Performance to similar colours was better at shorter distances, whereas performance to dissimilar colours was better at long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(62 citation statements)
references
References 32 publications
4
58
0
Order By: Relevance
“…The results presented in this paper extend previous findings of spatial distance effects on similarity ratings (Casasanto, 2008) and response times (Boot & Pecher, 2010) to incremental language processing. They also provide strong evidence for the role of spatial information in abstract language comprehension in agreement with theories of grounded cognition (see Lakoff & Johnson, 1999).…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…The results presented in this paper extend previous findings of spatial distance effects on similarity ratings (Casasanto, 2008) and response times (Boot & Pecher, 2010) to incremental language processing. They also provide strong evidence for the role of spatial information in abstract language comprehension in agreement with theories of grounded cognition (see Lakoff & Johnson, 1999).…”
Section: Resultssupporting
confidence: 79%
“…Response times were shorter when colored squares were similar and close to each other (vs. far apart), and when differently-colored squares were far apart (vs. close to each other). Together, Boot and Pecher (2010) and Casasanto's (2008) findings suggest that representations of spatial distance are mapped onto the more abstract concept of similarity and that this mapping modulates offline behavioral measures.…”
Section: Visuo-spatial Representations and Abstract Concepts: Spatialmentioning
confidence: 99%
See 1 more Smart Citation
“…The most influential one is probably the Conceptual Metaphor Theory, which states that abstract concepts are represented by image schemas derived from concrete domains. Evidence supporting this theory has shown for example that similarity is represented as closeness, categories as containers, and that the abstract notion of time is mapped onto the concrete domain of space (e.g., Lakoff and Johnson, 1980; Gibbs and Steen, 1999; Boroditsky and Ramscar, 2002; Casasanto and Boroditsky, 2008; Boot and Pecher, 2010, 2011; Casasanto et al, 2010; Flusberg et al, 2010; Lai and Boroditsky, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Research has also focused on how the relationships between two object representations might influence the relationships observed between two physical objects. Casasanto (2008) as well as Boot and Pecher (2010), for instance, reported that spatial proximity affects people's similarity judgments of corresponding concepts such that two objects standing close to each other are perceived as being more similar than two objects standing far from each other. Nevertheless, similarity studies have never explored the structure of within-category psychological space.…”
mentioning
confidence: 99%